Predictors of 2-year post-discharge mortality in hospitalized older patients - Werner, Christian; Sturm, Melanie; Heldmann, Patrick; Fleiner, Tim; Bauer, Jürgen M.; Hauer, Klaus (Journal of Clinical Medicine, 2024)
Background: Understanding prognostic factors for adverse health outcomes is clinically relevant for improving treatment decision-making processes, potentially leading to enhanced patient prognosis. This secondary analysis of a prospective observational study aimed to identify independent factors associated with 2-year post-discharge mortality in acutely hospitalized older patients. Methods: All-cause mortality and date of death of 115 patients (83.3 ± 6.3 years, females: n = 75, 65.2%) admitted to acute geriatric wards were determined two years after hospital discharge through telephone interviews. Potential prognostic factors measured at hospital admission included demographic and clinical characteristics, nutritional, cognitive, and psychological status, Fried frailty phenotype, functioning in activities of daily living, locomotor capacity, and 24 h in-hospital mobility and objectively measured physical activity (PA) behaviors. Results: The 2-year mortality rate was 36.7% (n = 41). Univariate and multivariate Cox proportional hazards regression models revealed that mean daily PA level (hazards ratio (HR) = 0.59, 95% confidence interval (CI) 0.90-1.00; p = 0.042), frailty (HR = 3.39, 95% CI 1.20-9.51; p = 0.020), and underweight, in contrast to overweight (HR = 3.10, 95% CI 1.07-9.01; p = 0.038), at hospital admission were independently predictive of post-discharge mortality. Conclusion: PA, frailty, and underweight at hospital admission should be considered when evaluating long-term survival prognosis, establishing risk profiles, and developing personalized care pathways in acute hospital care of older adults.